Association between Knowledge about How to Search for Mental Health Information and Emotional Distress among Older Adults: The Moderating Role of Immigration Status. Issue 1 (17th February 2020) - Nakash, Ora; Hayat, Tsahi; Abu Kaf, Sarah; Cohen, Michal
ABSTRACT: Mental health literacy (MHL) provides a framework to overcome barriers to service use and reduce mental health disparities through public education. Acquiring basic knowledge about mental health problems can guide subsequent help-seeking behavior. Improving knowledge about how to search for mental health information is a critical first step in improving MHL. In this study, we examined the association between knowledge about how to search for mental health information and emotional distress among older adults. We further examined the moderating role of immigration status in this association. A sample of 605 older adults participated in the study (N = 357 Native Israelis; N = 222 Immigrants from the Former Soviet Union). Participants completed self-report measures assessing MHL and emotional distress. Our findings show that Native Israelis reported significantly lower levels of emotional distress and higher levels of knowledge about how to search for mental health information compared to immigrants. Moreover, while among native older adults, increased knowledge about how to search for mental health information was associated with lower emotional distress, among immigrant seniors there was no significant association between these variables. Our findings suggest that differences among immigrant and native older adults can impact the effectiveness of the mental health knowledge that is accessed.